Design and implementation of autonomous control systems - Doraiswami, R.; Diduch, C.P.; Kuehner, J. (Conference proceedings - IEEE International Conference on Systems, Man, and Cybernetics, 1998)
An integrated approach is proposed for the design and implementation of autonomous control systems that unifies the design problems of failure detection, isolation and accommodation. The system consists of an interconnection of components that are subject to failure. A component fault occurs when one or more of the component parameters change. The paper describes a scheme for: 1) detecting when one of the components fail, 2) identifying the failed component and 3) under certain conditions accommodating the failure by controller tuning. The problem is compounded by the restriction that only the inputs and outputs of a limited number of components can be measured. Therefore it is not possible to directly determine the diagnostic parameters using parameter identification theory. The detection problem is solved using an observer. The isolation (FDI) problem is posed as a pattern classification problem that is solved using the Bayes decision strategy and a geometric analysis. Once a fault is isolated we show how a linear feedback controller may be tuned to minimize an integral squared error performance criterion using a gradient-based algorithm.